Granulomatous Thyroiditis Diagnosed by Fine-Needle Aspiration Cytology—A Case Report With Review of Other Benign Thyroid Entities. Issue 3 (May 2015) - Kanber, Yonca; Auger, Manon
Abstract : Abstract: Fine-needle aspiration cytology is important in the evaluation of thyroid nodules; its results guiding management and often reducing unnecessary surgery to the patients harboring benign nodules. Most thyroid nodules are benign, and the most commonly aspirated lesion is the benign follicular nodule. Other benign conditions include inflammatory and autoimmune disorders. This review discusses the clinical and cytological findings of various benign entities involving the thyroid gland, including benign follicular nodule, Graves disease, lymphocytic (Hashimoto) thyroiditis, suppurative thyroiditis, Riedel thyroiditis, and granulomatous (subacute, de Quervain) thyroiditis; a case report of the latter is presented.